Consultative Group to Assist the Poor - Independent Evaluation Group (Washington, DC: World Bank, 2017)
This is the Global Program Review (GPR) of the Consultative Group to Assist the Poor (CGAP). Established in 1995 as a consortium of public and private donors with its secretariat located in the World Bank, the mission of CGAP has been to help build efficient local financial markets that are integrated into the mainstream financial system and that serve all the unbanked, including very poor and harder-to-reach clients with ever more innovative, convenient and affordable financial services. Its specific objectives have been to generate and disseminate knowledge, to catalyze the movement toward good-practice performance standards, and to build consensus among its many and varied stakeholders. In pursuit of these objectives, CGAP's generic activities have consisted of: (a) providing advisory services, (b) developing and setting standards, (c) advancing knowledge (including sector intelligence and information sharing), and (d) offering training and capacity building services.